ANALYSIS OF USER SATISFACTION LIBRARY ONLINE CATALOG AT UPN VETERAN EAST JAVA USING EUCS METHOD - Khansa Renata; Arista Pratama; Anita Wulansari (Fakultas Teknik Universitas Lambung Mangkurat, 2022)
The development of information technology in this digital era has prompted numerous changes in many aspects of life, notably in the field of libraries, that are necessary to satisfy the demands of librarians to locate information easily, quickly, and precisely. OPAC (Online Public Access Catalog), often known as Online Catalog, is a website-based catalogue system used to search for information on library materials so they may be accessible whenever and wherever. One of the academic libraries that have used the Online Catalog is Universitas Pembangunan Nasional